Evaluation of health belief model-based educational intervention on colorectal cancer screening behavior at South Khorasan, Iran - Shahrbanoo Khazaei; Fatemeh Salmani; Mitra Moodi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Colorectal cancer is the most common cancer of the gastrointestinal tract. Health beliefs play an important role in the development of health behaviors. In this study, the effect of educational intervention based on Health Belief Model on colorectal cancer screening behavior was investigated. MATERIALS AND METHODS: This study was performed as a randomized controlled intervention. The study population was 50-70-years old in Khosf city. Initially, 120 eligible populations were randomly divided into intervention and control groups (60 people in each group). The data collection tool was a standard colorectal cancer screening questionnaire that was completed before, immediately, and 3 months after the intervention. The intervention consisted of eight 60-min training sessions. The collected data were analyzed using SPSS19 software and statistical tests. RESULTS: The mean age of the intervention and control groups was 63.53 ± 5.67 and 57.73 ± 5.77 years. In terms of mean scores of knowledge, perceived susceptibility, perceived severity, and perceived barriers were homogeneous before intervention. After the intervention, the mean score of the model constructs showed significant changes, which was statistically significant (P < 0.05). The rate of occult blood test in stool 3 months after training reached 90% in the intervention group and 15% in the control group. CONCLUSIONS: The results of this study showed that by taking measures to reduce perceived barriers as well as increase knowledge, perceived susceptibility, severity, benefits and self-efficacy, the rate of participation in occult blood testing in feces can be significantly increased.